An approach for estimating haplotype diversity from sequences with unequal lengths. Issue 9 (25th June 2021) - Fan, Ping; Fjeldså, Jon; Liu, Xuan; Dong, Yafei; Chang, Yongbin; Qu, Yanhua; Song, Gang; Lei, Fumin
Abstract: Genetic diversity is an essential component of biodiversity. Developing robust quantification methods is critically important in depicting the genetic diversity underlying the geographical distributions of species, especially for the sequence data with unequal lengths. Traditional calculation of genetic diversity depends on sequences of equal length. However, many homologous sequences downloaded from online repositories vary in length, posing a significant challenge to quantify the genetic diversity, especially haplotype diversity. We developed a new approach independent of sequence length by applying the same parameters used in calculating nucleotide diversity to estimate haplotype diversity. We compared this novel approach with the calculations by the program DNAsp, and we used simulation data from terrestrial vertebrates (birds, mammals and amphibians) and Homo sapiens to validate the method's performance. We further applied this approach to explore the global latitudinal gradients of haplotype diversity in amphibians, mammals and birds, and compared the results by traditional methods. The haplotype diversity calculated by our novel approach is consistent with the results from DNAsp. The simulations showed that our approach is robust and has a good estimating performance for sequence data with unequal lengths. For the datasets of terrestrial vertebrates and H. sapiens, our approach is capable of estimating haplotype diversity with unequal intraspecific sequence lengths. In contrast to patterns based on traditional methods, we observed different latitudinal patterns of haplotype diversity between the northern and southern hemispheres for terrestrial vertebrates, which is consistent with the updated pattern of nucleotide diversity for mammals. The present work contributes to the development of more precise quantification methods, which may be broadly applied to assessing biogeographical patterns of genetic diversity. 摘要: 遗传多样性是生物多样性的重要组成部分, 建立稳健的定量计算方法对于遗传多样性地理分布格局的研究至关重要。 传统遗传多样性的计算方法依赖于同源区域长度一致的DNA序列。然而公共数据库中的大量基因序列的长度是不一致的, 这为遗传多样性尤其是单倍型多样性的定量评估带来了极大的挑战。我们开发了一种利用核苷酸多样性来计算单倍型多样性的方法, 并通过比较该方法与遗传多样性常用分析软件DNAsp得到的结果来验证方法的准确性。随后我们基于现有基因序列的模拟, 评估了该方法对于陆生脊椎动物 (两栖类, 鸟类、哺乳类) 和人类不同重叠区域的基因遗传多样性的计算性能。作为一个应用示例, 我们以鸟类、哺乳类和两栖类为研究对象探讨了单倍型多样性的分布格局。 我们的方法得出的单倍型多样性的结果和DNAsp的分析结果一致。模拟分析表明我们的方法对于不同重叠长度的序列具有可靠的评估性能。 该方法适用于不同长度序列数据, 弥补了现存方法仅能计算长度相同序列数据的单倍型多样性的缺陷。与传统方法相比, 我们发现脊椎动物单倍型多样性的分布格局在南北半球间存在差异, 这与更新的哺乳动物核苷酸多样性格局类似。我们的结果有助于发展更精确的定量方法以评估遗传多样性的地理格局。